PROFILE OF LABORATORY AND IMPLEMENTATION OF MA PRACTICUM IN THE REGION OF KARAWANG DISTRICT - Vionira Agnyi; Imelda Helsy; Sari Sari (UIN Sunan Gunung Djati Bandung, 2021)
Research has been carried out using a descriptive method with a qualitative approach. The purpose of this study is to obtain data regarding the suitability of the profile of the completeness of tools and materials, arrangement of tools and materials, laboratory administration, furniture and educational media, as well as the implementation of laboratory practicum, which will then be used as the basis for policy making to the authorities. The instruments used were questionnaires, observation sheets and interview sheets to chemistry teachers and laboratory coordinators. The results of this study indicate that the availability of tools is included in the complete category (60%) and the availability of complete materials (72%). The administration of tools and materials is in the complete category (72%) and the labor administration is in the very complete category (85%). Furniture and educational media belong to the very complete category (77%). Furthermore, practicum implementation is included in the good category (52%).